EVALUASI PEMBELAJARAN DALAM AL-QUR’AN: ANALISIS TERHADAP SURAT AL-BAQARAH AYAT 31-34 - Siti Nurcholida; Mashudi; Saihan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This article aims to analyze the content of Surah Al-Baqarah verses 31–34, which discusses evaluation based on three aspects: the cognitive aspect, the affective aspect, and the psychomotor aspect. This study is a library research study, meaning it uses library sources such as books, journals, and articles to analyze and support the examination of the content of Surah Al-Baqarah verses 31–34 regarding evaluation. The data analysis method employed is content analysis. The results of the study indicate that there are three aspects of evaluation in Surah Al-Baqarah verses 31–34. First, the cognitive aspect (knowledge) is demonstrated by Allah SWT teaching Prophet Adam the names of all things, and by Prophet Adam’s ability to remember, understand, and apply the knowledge that Allah SWT had taught him. Second, the affective aspect (attitude or emotion) is shown by the angels who sincerely acknowledged their lack of knowledge and demonstrated an attitude of reverence toward the greatness of Allah SWT. Finally, the psychomotor aspect (skills) is demonstrated by the angels who prostrated to Prophet Adam by Allah SWT’s command, except for Iblis.